Exploring the challenges to investigating antibiotic resistance along the pork value chain in Viet Nam and the benefits of the One Health approach - Mitchell, M.E.V. (University of Sydney, 2018)
Background Antibacterial resistance (ABR) is a global health crisis, which threatens the ability to treat diseases and complicate medical procedures. The Vietnamese government have recognised the multifaceted risk ABR poses to human health and the country’s sustainable development and are in the process of developing a surveillance system for ABR. However, the implementation of policies that require inter-sectoral collaboration can be challenging. This project aimed to explore the experiences of actors in the animal health and human health sector to elucidate their perspectives and experiences of investigations in addressing ABR along the pork-value-chain in Viet Nam.